Prospects for Open Heavy Flavor Measurements in Heavy Ion and p+A Collisions in a Fixed-Target Experiment at the LHC - Daniel Kikoła (Advances in High Energy Physics)
High luminosity data in a fixed-target experiment allow studying interactions of heavy quarks with nuclear matter in the intermediate energy range with extremely high precision. We present a feasibility study for open charm and bottom production measurements in the energy range of a fixed-target experiment at the LHC (AFTER@LHC). We demonstrate, that high-precision data from AFTER will allow answering two open questions: if there is a collective behavior of charm quarks in p+A collisions at RHIC energy and if charm production is suppressed in the energy range of sNN = 60–80 GeV. We argue that simultaneous measurement of D0 suppression as a function of traverse momentum at midrapidity and forward rapidity can help to pin down the mechanism of charm energy loss in the hot and dense nuclear medium.